FEATURES OF VITAMIN D METABOLIC METHODS AND ITS CONTRIBUTION TO THE DEVELOPMENT OF METABOLIC SYNDROME IN CHILDREN - Garifulina, Lilya; Ashurova, Maksuda (Medical science of Uzbekistan, 2025)
The original article presents the results of a study of the metabolic state and cholecalciferol concentration in children and adolescents who are overweight and obese, determining the role of vitamin D in the formation of metabolic syndrome in children and adolescents. The results of the study are recommended for widespread implementation in the practice of general practitioners in central district primary health care clinics. The aim of the study was to determine the state of metabolism and concentration of cholecalciferol in overweight and obese children and adolescents, with the determination of the role of vitamin D in the formation of metabolic syndrome in children and adolescents. Materials and methods: 106 children and adolescents with exogenous constitutional type of obesity, as well as 30 children and adolescents with normal body weight were examined. A complex of anthropometric, clinical, biochemical, enzyme immunoassay studies was conducted to determine the level of carbohydrate and lipid metabolism, as well as vitamin D. Results of the study: it was revealed that the pathology of carbohydrate metabolism in overweight and obese children and adolescents occurs in 47.6% of cases, an imbalance of lipid metabolism – in 38.6%, insufficiency and deficiency of cholecalciferol in blood serum – in 76.9% of cases of severe obesity. The results allowed us to establish the presence of metabolic syndrome in 58.4% of children with signs of abdominal obesity, while its complete variant was observed in 20.9%. Children with metabolic syndrome have the greatest vitamin D deficiency. Conclusion: serum cholecalciferol is a risk factor for the initial imbalance of metabolic processes with the formation of a further symptom complex of metabolic syndrome.